Memorias en el Ejército Argentino: fragmentos de un relato abierto - Máximo Badaró (Centre de Recherches sur les Mondes Américains, 2012)
This article presents intermixed fragments of institutional policies of the Argentine army and individual experiences of its members linked to the ways the memories of Argentina’s recent past, particularly the army’s performance during the last military dictatorship, are present in this institution. The article shows a representation about this past that, while having a certain unity within the military institution, presents a fragmented and open form that not only speaks of the military dictatorship and other periods in Argentina’s history but also of the ways current army officers, especially the younger, experience the Argentine military transformations in democratic times.